(untitled) (Comprehensive Journal of Science, 2024)
Software-Defined Wide Area Network (SD-WAN) has revolutionized the way organizations manage their WAN infrastructure. By centralizing control, providing intelligent path selection, and integrating advanced security features, SD-WAN offers significant benefits in terms of agility, cost-effectiveness, and performance. This paper delves into the fundamental concepts of SD-WAN, its key components, and its operational mechanisms. It then conducts a comparative analysis of two leading SD-WAN solutions: Cisco SD-WAN and Fortinet SD-WAN, highlighting their strengths, weaknesses, and suitability for different organizational needs.